New species of the genus Nipponeurorthus Nakahara, 1958 (Neuroptera: Nevrorthidae) from China - Liu, Xingyue; Aspöck, Horst; Aspöck, Ulrike (Zootaxa, 2014)
The lacewing family Nevrorthidae is one of the most mysterious groups of Neuroptera. Here we describe two new species of the genus Nipponeurorthus Nakahara, 1958 from China, namely Nipponeurorthus damingshanicus sp. nov. and Nipponeurorthus furcatus sp. nov. A key to the species of Nipponeurorthus is provided. Phylogenetic and biogeographic considerations on Nipponeurorthus are summarized.